2020
DOI: 10.29133/yyutbd.688772
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Utilization of Mechanization in the Agricultural Enterprises in Terms of Productivity

Abstract: Productivity in agricultural enterprises is mainly achieved by increasing the productivity of seed, fertilizer, pesticide, labor and mechanization inputs. The aim of this study was to determine the productivity of the use of mechanization which has a significant share and limitation in production costs. For this purpose, in Karapınar, Çumra and Altınekin districts, which have 24% of the mechanization equipment used in the province of Konya, work was carried out. According to stratified random sampling method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The carried out research gives grounds to state that the problem of cost management of agricultural enterprises is very relevant since it is widely represented in the studies of many scientists. In particular, it has been established that efficient cost management of agricultural enterprises is one of the key prerequisites for ensuring the sustainable development of these enterprises (Markina et al [5] stressed the importance of an appropriate level of mechanization, availability of agrarian capacities, the appropriate level of supply of resources, etc., which reduces the costs of agrarian enterprises and Agizan et al [5]. The research of Bayramoglu et al [8] has stated that ensuring efficient cost management of agricultural enterprises is one of the important components of achieving the economic sustainability of these enterprises.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carried out research gives grounds to state that the problem of cost management of agricultural enterprises is very relevant since it is widely represented in the studies of many scientists. In particular, it has been established that efficient cost management of agricultural enterprises is one of the key prerequisites for ensuring the sustainable development of these enterprises (Markina et al [5] stressed the importance of an appropriate level of mechanization, availability of agrarian capacities, the appropriate level of supply of resources, etc., which reduces the costs of agrarian enterprises and Agizan et al [5]. The research of Bayramoglu et al [8] has stated that ensuring efficient cost management of agricultural enterprises is one of the important components of achieving the economic sustainability of these enterprises.…”
Section: Discussionmentioning
confidence: 99%
“…Kocaköse et al [4] also emphasize that an important role in the context of reducing costs, particular production costs, agricultural enterprises play the relevant factors of influence, namely: 1) the level of mechanization; 2) availability of irrigation facilities; 3) the level of supply of resources; 4) features of sales; 5) product prices; 6) prices for raw materials; 7) labor resources. Agizan et al [5] emphasize the importance of mechanization as one of the key factors in the development of agricultural production. Panagos et al [6] argue that agricultural enterprises often face the problem of loss of productivity of agricultural production due to soil erosion, which affects the growth of direct costs of these enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rural infrastructure defects such as increased fragmentation, fragmentation of parcels, road inadequacy, loss of time cause delays in planting time and prevent parcels from benefiting from infrastructure facilities (Latruffe and Piet, 2014;Yucer et al, 2016;Kuslu, 2019;Sardar et al, 2019;Ağızan et al, 2020;FAO, 2020;Kuzu and Değirmenci, 2020). At the end of all these, the desired product increase cannot be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Radish is generally consumed raw in garnishes and salads, but in some countries, it is also consumed cooked, pickled, or dried. Radish, which has an important place in human nutrition, is rich in A, B and C vitamins, minerals such as calcium, phosphorus, potassium and iron, and antioxidant substances (Akan et al, 2013). Radish is also of great importance in terms of human health (Chung et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Radish is also of great importance in terms of human health (Chung et al, 2012). It is reported that radish can be evaluated as a functional food due to the compounds it contains and its contribution to human health (Akan et al, 2013). Soil properties have a great effect on the formation of quality roots in radish.…”
Section: Introductionmentioning
confidence: 99%